A computational approach to investigate constitutive activation of NF‐κB - Mobeen, Ahmed; Puniya, Bhanwar Lal; Ramachandran, Srinivasan (Proteins, structure, function, and bioinformatics, 2022)
Nuclear factor kappa B (NF‐κB) signaling is the master regulator of inflammatory pathways; therefore, its regulation has been the subject of investigation since last two decades. Multiple models have been published that describes the dynamics of NF‐κB activity by stimulated activation and feedback loops. However, there is also paramount evidence of the critical role of posttranslational modifications (PTMs) in the regulation of NF‐κB pathway. With the premise that PTMs present alternate routes for activation or repression of the NF‐κB pathway, we have developed a model including all PTMs known so far describing the system behavior. We present a pathway network model consisting of 171 proteins forming 315 molecular species and consisting of 482 reactions that describe the NF‐κB activity regulation in totality. The overexpression or knockdown of interacting molecular partners that regulate NF‐κB transcriptional activity by PTMs is used to infer the dynamics of NF‐κB activity and offers qualitative agreement between model predictions and the experimental results heuristically. Finally, we have demonstrated an instance of NF‐κB constitutive activation through positive upregulation of cytokines (the stimuli) and IKK complex (NF‐κB activator), the characteristic features in several cancer types and metabolic disorders, and its reversal by employing combinatorial activation of PPARG, PIAS3, and P50‐homodimer. For the first time, we have presented a NF‐κB model that includes transcriptional regulation by PTMs and presented a theoretical strategy for the reversal of NF‐κB constitutive activation. The presented model would be important in understanding the NF‐κB system, and the described method can be used for other pathways as well.